Building bridges in educational territories: Peace education, gender and LGBTQIA+ sexualities - Prudenciano de Souza, Cristiane (Aprender, 2025)
This article explores the intersection between educational territories, peace education, gender and LGBTQIA+ sexualities, analyzing the potential and challenges of inclusive pedagogical practices. Based on a literature review, it contrasts the concept of educational territory with the panopticon model. It highlights the potential of the educational territory concept as a space for critical observation and dialog. It argues how it can contribute to the formation of critical and respectful individuals in the face of diversity, playing an important role in building more equitable environments. The central proposal is to understand how these links can promote coexistence based on the precepts of peace education, questioning violence of gender and sexuality and replacing them with practices of gender equity and respect for diversity. In this context, we intend to contribute the intersecting concepts to the construction of a cultural heritage that praises the principles of peace, values different ways of life, strengthens plurality and collaborates in the consolidation of a society based on the principles of democracy.